Gulf Bluestem, Maritime Bluestem, Schizachyrium maritimum - Debbie Miller; Mack Thetford; Chris Verlinde; Gabriel Campbell; Ashlynn Smith (EDIS)
Gulf bluestem occurs throughout the Florida Panhandle and in neighboring coastal states. Gulf bluestem helps stabilize dunes, forms thick stands in areas leeward of slopes (Craig 1991), replaces sea oats as the dominant species on protected foredunes behind a seaward ridge after 2 to 17 years (Johnson 1997), and occurs throughout flatwoods and disturbed areas. This plant is very closely related to little bluestem (Schizachyrium scoparium), and its taxonomic position is not entirely agreed upon by taxonomists; hence information may also be located using the taxonomic synonym Schizachyrium scoparium var. scoparium. https://edis.ifas.ufl.edu/sg184